The use of Small Group Work techniques for improving reading comprehension - An Nisaa Rahmadani (Universitas Syiah Kuala, 2017)
The aims of this research were to find out (1) whether there was a significant difference in students’ reading comprehension abilities in terms of main idea, vocabulary, detailed information, and inferences for students who were taught using the Small Group Work (SGW) technique compared to those taught through a standard technique. And (2) to find out if the use of the SGW technique motivated students studying reading comprehension to read more compared to other students. The sample for this research was class VIII(1) and VIII(2) from the second year at SMPN 1 Baitussalam in Aceh Besar in the academic year 2014/2015. This research used true experimental design. The result of this study using the SGW technique showed that there was no significant difference in the students’ reading comprehension in terms of the main idea. The use of the SGW technique did not motivate and did not encourage the experimental group students to develop their reading comprehension abilities.